2007
DOI: 10.1590/s0102-311x2007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Mental State Examination norms in a community-dwelling sample of elderly with low schooling in Brazil

Abstract: The objective of this study was to assess Mini-Mental State Examination norms of a functionally normal sample of community-dwelling elderly. Illiterate and low-educated subjects who scored less than 5 on the Pfeffer Functional Activities Questionnaire (PFAQ) [n = 397; female = 269; mean age = 72.15 (SD = 7.24) years] had the 5th, 25th, 50th, and 75th percentiles calculated according to age (65-74; 75-84 years). Overall MMSE score was 21.97 (SD = 4.48). Mean MMSE for illiterate younger individuals was 19.46 (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
1
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 21 publications
(32 reference statements)
2
45
1
18
Order By: Relevance
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
“…Scores on MMSE are greatly influenced by age and education level (13)(14)(15). Cognitive impairment and dementia have been associated with rural dwellers (16), increased rates of hospitalization (17,18), increased risk for falls (19,20), increased prevalence of fear of falling (21,22), diabetes mellitus (23,24), depression (17,25), and dependence in activities of daily living [ADL] (26).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several strategies have been proposed in order to minimize the effects of schooling level in the interpretation of results, such as: (1) adjustment of cut-off points according to schooling level [5][6][7][8] , (2) the use of cut-off points based on the distribution of MMSE scores in the study population 9 and (3) transcultural adaptation [10][11][12] . In Brazil, the most common approach has been the use of different cut-off points according to schooling level.…”
mentioning
confidence: 99%
“…when score distribution is used to establish cut-off points, the most recommended approach is to consider that subjects with scores below the 5 th percentile have a high probability of dementia 13,14 and to use the lower quartile as the cut-off for cognitive screening 9,15 . In Brazil, the 5 th percentile was used to define the cut-off points in a study of patients aged 15 years or more at a general hospital triage 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation